Mapping the Concept of Sustainable Consumption: An Analysis From the Adoption and Promotion of Pro-Environmental and Social Behaviors in University Students - Arias, Claudia; Vélez-Rolón, Adela M.; Méndez-Pinzón, Manuel (Frontiers in Education, 2021)
The concept of sustainable consumption has been described in the literature from different perspectives, but few have focused on defining the consumer perspective and strategies to appropriate this knowledge and behaviors in the classroom, which becomes a major challenge in times of covid 19 and confinement. This article proposes an approach to the concept by university students from the implementation of a pedagogical strategy, which involved the implementation of a virtual learning community and the evaluation of the understanding of this concept through the use of mind maps (pre and post). Through the mind maps, data were collected to evaluate the understanding of the concept, the analysis of semantic richness and systemic complexity. The results show the associations established by the students, proposing a categorization system arising from the data and the previous literature review. The study concludes that the students broadened their vision of sustainable consumption in terms of the actors involved, consumption decisions and the social and environmental dimensions of sustainability